Considerations on the Use of Exogenous Fibrolytic Enzymes to Improve Forage Utilization - Germán D. Mendoza; Octavio Loera-Corral; Fernando X. Plata-Pérez; Pedro A. Hernández-García; Mónica Ramírez-Mella (The Scientific World Journal)
Digestion of cell wall fractions of forage in the rumen is incomplete due to the complex links which limit their degradation. It is therefore necessary to find options to optimize the use of forages in ruminant production systems. One alternative is to use exogenous enzymes. Exogenous fibrolytic enzymes are of fungal or bacterial origin and increase nutrient availability from the cell wall, which consists of three fractions in different proportions depending on the species of forage: digestible, potentially digestible, and indigestible. The response to addition of exogenous enzymes varies with the type of forage; many researchers infer that there are enzyme-forage interactions but fail to explain the biological mechanism. We hypothesize that the response is related to the proportion of the potentially digestible fraction. The exogenous enzyme activity depends on several factors but if the general conditions for enzyme action are available, the potentially digestible fraction may determine the magnitude of the response. Results of experiments with exogenous fibrolytic enzymes in domestic ruminants are inconsistent. This, coupled with their high cost, has made their use unattractive to farmers. Development of cheaper products exploring other microorganisms with fibrolytic activity, such as Fomes fomentarius or Cellulomonas flavigena, is required.